Методология испытаний устойчивости технических средств к действию магнитного поля молнии - Князев, В. В.; Чернухин, А. Ю.; Шаламов, С. П. (ХНУРЕ, 2018)
The object of the study is the effect of the magnetic field accompanying lightning on echnical means, which are based on electronic, radio-electronic and electrotechnical components. The aim of the work is the methodology for determining the stability of technical means to the effect of a magnetic field of lightning in accordance with the requirements of the standard MIL-STD- 464C:2010. The paper presents the results of the preparation of the equipment for testing the stability of the technical means.
Keywords: испытания; магнитное поле; устойчивость к действию молнии